Analisis Relasi Fenomena Kriminalitas Dengan Kebijakan Publik - Iwansyah, Henry (As-Siyasi: Journal of Constitutional Law, 2021)
This study revealed the phenomenon of crime in North Lampung Regency, Lampung Province. The aim, in addition to getting a complete picture, is to analyze the relationship between empirical phenomena and local government policies. This type of research is "descriptive-analytic" using a qualitative approach. The techniques used are mostly based on in-depth interviews, documentation, observation and focus group discussion. The results of the study show that the crime rate in North Lampung Regency in the past 5 (five) years was quite alarming, although in the 2017-2018 range there was a significant downward trend.This decrease was caused by (1) District Government policies in the field of public security, which were implemented in the form of intensive government apparatus (police) in effort to eradicate crime, and (2) policies in the field of non-Public Security in the form of developing a creative economy and youth coaching. This study concludes that out of the 2 (two) types of policy, the handling of the public security sector is only effective in tackling crime for short-term needs. While for long-term needs, the District Government needs to develop a policy of economic development based on local potential.